Clean, Diversified, and Affordable Energy for the European Union in the Context of the REPowerEU Plan - Vasile Dinu (Amfiteatru Economic)
Since the establishment of the Recovery and Resilience Facility, the geopolitical context has changed considerably. The Russian invasion of Ukraine has had a drastic impact on the society and economy of the European Union. Additionally, amid a global economic outlook of economic stagnation and rising inflation, geopolitical challenges are unprecedented. One of the solutions proposed from the first days of the armed conflict in Ukraine was to reduce the EU’s dependence on fossil fuels imported from Russia. The European Commission and the Member States of the European Economic Community have as their point of reference the ‘Fit for 55’ solution package of the European Green Deal, as well as increasing the use of renewables and further improving energy efficiency. On 18 May 2022, the Commission published that REPowerEU Plan the sets out joint European action in this area, complementing the measures taken regarding the security of supply and energy storage. The measures included in the REPowerEU plan enable energy savings by diversifying energy supply and accelerating the development of renewable energy that would replace fossil fuels in homes, industry, and electricity generation. In this way, the phasing out of fossil fuel imports from Russia will be accelerated. This will also reduce electricity prices and fossil fuel imports over time.